KAWIN PAKSA (Problem Kewenangan Wali dan Hak Perempuan dalam Penentuan Jodoh) - Abu Bakar (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2010)
Religion teaching is connected with the forms of such as thefreedom of choosing, deciding, and doing or not doingsomething in positive way. Unfortunately, the freedom oftencauses the problem in implementation, such as the freedom ofchoosing or deciding the mate that often ends in the practice offorce marriage. It is a relational problem between parents andtheir children in deciding their children’s mate because both ofthem keep their wish stubbornly that claim as their rights. Theirparents think that they has authority in deciding their mate totheir children because they think ijbar right is theirs. On theother hand, the children also think that they have the right todecide their mate by themselves. Islam protects human rights ineverything including the right to their daughter in decidingtheir mate.